Study and Prediction of Ionic Liquid Viscosity Via Means of Quantitative Structure-Property Relationship - Somasundaram, Shoban Raj (IRC, 2016)
Ionic Liquid (ILs) is regarded as green chemical and ready to replace other non environmental friendly solvents. Viscosity of ILs is a very important measure to consider in order for the ILs to be used widely in the industry due to its significance in the chemical processes. This makes knowing the viscosity of ILs becomes more important than ever. However, the availability of ILs viscosity data is not sufficient enough due to the synthesis of new ILs increases drastically time to time. Hence, predicting the ILs viscosity prior to production is best approach to overcome this problem.